Manajemen Dalam Persepektif Al-Qur’an (Kajian Tafsir) - Buyung Saroha Nasution (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This journal is entitled Management According to the Perspective of the Qur'an, Study of Tafsir. This journal studies the verses of the Koran about management in the study of interpretation. In compiling this paper, the author collects verses from the Qur'an about management, collects literature related to management, then the author conducts a study of several books of interpretation, and analyzes the opinions of various commentators. The systematics of writing are Introduction, Definition of Management, Management Theory, Management According to the Perspective of the Qur'an, Study of Interpretation and Conclusions.